The gondola Philadelphia and the Battle of Lake Champlain - Bratten, John R. (Studies in nautical archaeology, 2002)
"A veteran of the American Revolutionary War, the Continental gondola Philadelphia is the oldest intact warship currently on display in North America. After its recovery from the bottom of Lake Champlain in 1935, the fifty-four foot long Philadelphia, armed with three cannon and eight swivel guns, was moved to the newly constructed building housing what is now the National Museum of American History of the Smithsonian Institution. In this work, archaeologist John Bratten details the gunboat's history, construction, armament, tools, utensils, personal items, and rigging elements. He takes advantage of contemporary records to describe the Philadelphia's artifacts and presents for the first time an analysis of photographs taken during the 1935 recovery of the boat. Finally, he assesses the replica Philadelphia II, built at the Lake Champlain Maritime Museum during 1989-91 in order to provide an opportunity to evaluate how the gondola was constructed, manned, sailed, and propelled by sweeps."--Jacket